Analysis of Challenges and Solutions in Developing Pedagogical Competence of Prospective Elementary School Teachers: A Systematic Literature Review - Astuti, Yuni Dwi; Rohmani; Yuni Dwi Astuti (urn:multiple://2988-7828multiple.v3i64)
Pedagogical  competence is an essential foundation for primary school pre-service teachers to conduct high-quality instruction. This study aims to systematically identify the main challenges faced by primary school pre-service teachers in developing pedagogical competence and to analyze effective solutions and strategies that have been implemented. The research method employed is a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. The data collection process was conducted in June 2025 through the Google Scholar database, with a publication range from 2020 to 2024. Search keywords were formulated using Boolean operators to combine core concepts, such as: ("pedagogical competence" OR "pedagogical ability") AND ("primary school pre-service teachers" OR "PGSD students"). The article selection process was conducted in stages: from the total initial search results, a screening was performed based on title and abstract relevance, followed by a full-text eligibility analysis based on strict inclusion and exclusion criteria, yielding 14 relevant articles for qualitative analysis. The thematic analysis results indicate that the main challenges include difficulties in applying theory to practice, limitations in mastering teaching materials, developing innovative learning media, and classroom management. The identified solutions encompass strengthening teaching practice programs (such as microteaching and peer teaching with intensive supervision), developing contextual teaching materials, and utilizing digital technology as a pedagogical tool. Although several solutions demonstrate effectiveness, this study highlights the need for continuous implementation improvement and identifies research gaps related to the long-term effectiveness of interventions, the influence of contextual factors within Teacher Education Institutions (TEIs), and the development of valid assessment instruments to measure the adaptive competence of pre-service teachers. These findings are expected to provide a basis for policy formulation and the refinement of preparation practices for higher-quality primary school pre-service teachers who are responsive to contemporary challenges.ES teachers